Relationship between Syllabus, Course Book and Materials - Abdurazzakova Khushnoza Sobirovna; Botirova Hakima (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The desire for education is rising in the modern era. To produce skilled workers in each area, various training techniques are utilized. It is easy to notice, particularly in the field of English. It goes without saying that teaching students requires both the teacher's resources and their strong skills. As a result, the instructor must employ a variety of handouts and books for his work. Different manuals are being made by the teachers and the government in order to teach English successfully. The reader will learn about the correct handling of manuals, their creation, their value in the classroom, and other topics in the article that follows.